(untitled) (The Research of Medical Science Review, 2025)
Background: The operating room (OR) is one of the most important areas of a hospital, playing a fundamental role in patient treatment and hospital revenue. OR performance depends not only on advanced equipment or skilled staff, but also on effective scheduling and timely decision-making. These factors not only affect patient outcomes but also reduce staff job satisfaction. Job satisfaction is a factor that can have a profound impact on the overall productivity of an OR. The results of the study will help hospital management in making effective policies. Objective: To analyze how scheduling and decision-making practices influence operating room productivity, while employee satisfaction influences this relationship as a mediating factor. Methodology: Data collected from registered operating room professionals such as surgeons, anesthesiologists, technologists, and scrub nurses in different hospitals through a structured questionnaire. Convenience sampling technique used and the sample size was 226. Data analyzed using SPSS (version 25) with detailed and inferential statistics such as correlation, regression and Anova. Results: The results showed that staff working in busier ORs — often doing 16 or more surgeries a week — felt the biggest impact from how schedules were organized. A well-structured scheduling process and collaborative decision-making were linked to higher productivity, better work–life balance, and a stronger sense of being valued. Job satisfaction came out as a key mediator, boosting overall efficiency and teamwork. In fact, improvements in scheduling and staff satisfaction explained more than half of the productivity outcomes. Conclusion: This study shows that OR productivity is about more than just schedules and numbers it’s about the people behind them. When staff have a say in scheduling, feel supported, and maintain a good work–life balance, the OR operates more efficiently. By focusing on these human elements, hospitals can build a culture where both staff and patients benefit, making every surgical experience safer, smoother, and more successful.